Evaluation of improvement in performance of FRP composite by using Al (OH3) as secondary reinforcement. Issue 1 (May 2021) - Meenakshi, C.M.; Ravi, Rajesh; Stephen Leon, J.; Selvaraj, M.; Manikandan, K.; Suresh, G.; Lavanya, R.
Abstract: Composites are the materials of this century, and it uses are predominately occupied in all areas, starts from kitchen utilities to aerospace sectors. Among different type of composite materials, the fiber reinforced polymeric (FRP) composite materials are the most used and accepted one. There are many researches undergoing to further improve the performance of these fiber reinforced polymeric composites. One of the proven methods for performance improvement is adding secondary reinforcement into the base matrix material. There are different types of secondary reinforcement like rice husk, MgCO3, Boron nitride powders, which are often used and their respective performance recorded by different researchers. In this work, laminate of size 300 X 300 mm with 3 mm thickness fabricated using hand layup method in which epoxy has been chosen as the base matrix material. The laminate consisting of 3 layers (Glass-Flax-Glass) with 2% wt of Al (OH3) as secondary reinforcement and compared with the mechanical properties without using secondary reinforcement. From the result we understood that the tensile strength and flexural strength of laminate is increased by the addition of secondary reinforcement.